1989
DOI: 10.1525/aeq.1989.20.4.04x0457o
|View full text |Cite
|
Sign up to set email alerts
|

Old Order Mennonite One‐Room School: A Case Study

Abstract: This case study describes the building, curriculum, students, teacher, and instructional methods of an Old Order Mennonite one-room school in Pennsylvania. It was found that the students spend most of their time working on individual assignments and that the Mennonite heritage permeates the school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…There are relatively few studies of education in the Schmiedeleut Hutterite communities (cf Hostetler 1974;Hofer 2004;Katz and Lehr 2014), and even fewer dealing specifically with education in Groffdale Conference Old Order Mennonite communities (cf Dewalt and Troxell 1989;Johnson-Weiner 2007). This article is a preliminary presentation of a theoretical framework for understanding education in these communities and in other plain Anabaptist communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are relatively few studies of education in the Schmiedeleut Hutterite communities (cf Hostetler 1974;Hofer 2004;Katz and Lehr 2014), and even fewer dealing specifically with education in Groffdale Conference Old Order Mennonite communities (cf Dewalt and Troxell 1989;Johnson-Weiner 2007). This article is a preliminary presentation of a theoretical framework for understanding education in these communities and in other plain Anabaptist communities.…”
Section: Discussionmentioning
confidence: 99%
“…The interviewees' concerns about their children's environment are an integral part of the communal ethos (Dewalt and Troxell 1989).…”
Section: Community Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…(Kraybill, 1989(Kraybill, , 2001. were also seen to be inherently corrosive of Amish values (Dewalt and Troxell, 1989;Waite and Crockett, 1997). 23 In Amish schools the core curriculum contains reading, spelling, geography, arithmetic, German, and penmanship (Dewalt and Troxell, 1989, 315).…”
Section: The Amishmentioning
confidence: 99%
“…Another explanation is that the social role of the school (and of the teacher) in the community is limited to giving children basic skills whereas religious education is undertaken by the church (Hurst and McConnell 2010;Nye 2013;Erbay 2013) 6 A study of a Mennonite one-room school showed that the teacher seldom praised students or offered other reinforcing feedback on students' work. This was explained as a part of the resistance of the individualist ethos, and viewing education as a communal and cooperative project (Dewalt and Troxell 1989). 7 Parents also commented that public school children were less disciplined and well behaved and respectful (Hurst and McConnell 2010).…”
mentioning
confidence: 99%